Religious talk online the evangelical discourse of muslims, christians, and atheists - Pihlaja, Stephen (Cambridge University Press, 2018)
In the online world, people argue about anything and everything - religion is no exception. This book explains how and why religious conflict occurs online and how people of different religious beliefs interact on social media. It will appeal to researchers and students in sociolinguistics and discourse analysis, particularly those working on social media and religious language.